1958
DOI: 10.1017/s0021859600031038
|View full text |Cite
|
Sign up to set email alerts
|

The use of progesterone and serum gonadotrophin (P.M.S.) in the control of fertility in sheep. II. Studies in the extra-seasonal production of lambs

Abstract: Section 11. A total of 189 ewes, of various breeds and crosses were used in slaughter experiments conducted in anoestrum during 1953–6. The ewes were of mixed ages, and included four lambs, aged 52–71 days.2. Ewes received P.M.S. in different combinations with progesterone to induce co-incident oestrus and ovulation. Progesterone was employed in three forms, as a solution in oil, as a micro-crystalline suspension and as fused pellet implants. One hundred ewes were injected with the oil solutions, eighty-five w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
1

Year Published

1963
1963
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
3
29
1
1
Order By: Relevance
“…(Gordon, 1958;Allen & Lamming, 1960), but the reasons for the failure of behavioural oestrus in these small groups of sheep are not understood. It has been shown in similar groups of sheep that the fertilization rate of maiden sheep which mated at induced oestrus was usually high (up to 88 %) but in lactating sheep it was low (0 %) (Allen & Lamming, 1959, 1960.…”
Section: Analysis Of Uterine Washings and Presentation Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Gordon, 1958;Allen & Lamming, 1960), but the reasons for the failure of behavioural oestrus in these small groups of sheep are not understood. It has been shown in similar groups of sheep that the fertilization rate of maiden sheep which mated at induced oestrus was usually high (up to 88 %) but in lactating sheep it was low (0 %) (Allen & Lamming, 1959, 1960.…”
Section: Analysis Of Uterine Washings and Presentation Of Resultsmentioning
confidence: 99%
“…It would seem, therefore, that there is some additional factor which interferes with conception and implantation in the lactating sheep. Gordon (1958) suggested that there was a failure of implantation in the lactating sheep and showed that fertility was markedly improved if the animals were mated at the oestrus following an induced ovarian cycle which thus simulated the 'silent heat' at the beginning of the normal breeding season. Allen & Lamming (1960) reported the presence of spermatozoa within the zona pellucida of ova recovered after the first induced oestrus but an absence of fertilization.…”
Section: Analysis Of Uterine Washings and Presentation Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant mare serum has been used to increase fecundity in the ewe during the breeding season (Robinson, 1951; Wallace, 1954;Gordon, 1958a), and to augment fertility during anoestrus (Dutt, 1953; Robinson, 1954;Gordon, 1958b). During the breeding season, pms is given on the 12th to 14th day after oestrus, when the production of progesterone by the corpus luteum may be expected to be declining or about to decline (Edgar & Ronaldson, 1958).…”
Section: Introductionmentioning
confidence: 99%